(untitled) (Revista de Ciências Agroveterinárias, 2019)
Soil use systems have the potential to alter organic carbon stocks and may remain stable, increase, or decrease relative to the area without anthropogenic interference. The objective of this study was to quantify and compare the total organic carbon stock, organic carbon associated with minerals, particulate organic carbon, and calculate the carbon management index in soils grown under different systems of use. The treatments were represented by six systems of soil use: native vegetation of cerrado, single rubber tree, rubber tree with pineapple, Brachiaria sp. with 30 years, a pasture of Brachiaria sp. with three years, and conventional planting system. In each system, soil samples were collected in the 0-10, 10-20 and 20-30 cm layers to evaluate soil carbon contents and stocks, and undisturbed samples with volumetric rings to estimate soil density. The results were analyzed by Scott-Knott test (p≤0.05). The total organic carbon and the grain size fractions of the organic matter showed to be a promising attribute for soil quality evaluation. Total organic carbon, particulate organic carbon, and organic carbon associated with minerals were higher for native vegetation, Brachiaria sp. 30 years, followed by systems with rubber trees. The calculated carbon management index indicated that the use of rubber trees adds benefits to the soil in the medium and long term, followed by the treatment with Brachiaria sp.